EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) DISERTAI FISHBONE DIAGRAM (FD) UNTUK MEMBERDAYAKAN KEMAMPUAN MENGANALISIS - Pinkan Amita Tri Prasasti (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2015)
The purpose of this study was to determine the effectiveness of a problem based learningmodel accompanied with Fishbone Diagram to empower the ability to analyse. This studywas a quasi-experimental study. The study used a one-group pretest-posttest design. Thepopulation of the study was all students of grade X of Public Senior High School 2Karanganyar in the academic year of 2013/2014. Sample was taken using cluster randomsampling technique with a sample of 36 students. The instrument used was questionnaire,observation sheets, interviews, and tests. The ability to analyze data was tested with theWilcoxon test and calculated by Ngain. The results showed the effectiveness of PBL moduleaccompanied with FD, in which it had been successful in increasing the ability to analysewith a value of Ngainof 0.71 and the result was significance at p = 0.000, making theability belong to “high” category. Based on the results of research and hypothesistesting, it can be concluded that PBL model with FD was effective in empowering theability to analyseof the tenth graders of.